(untitled) (Research, Society and Development, 2021)
This work is motivated by the research entitled Non-formal Environmental Education and Non-Governmental Organization of a social nature: incentive to future actions in communities in Rio Grande do Sul, through the Universidad Do Rio Grande by the Post-Graduate Program in Environmental Education. Therefore, an integrative review aims to understand how Non-Governmental Organizations understand, develop and practice EE. The review concludes that it is extremely important to think about Environmental Education through Non-Governmental Organizations, since these are intermediary channels between civil society and the State. In addition, it is clear that there are several and different types of Environmental Education practices in organizations, which include workshops, short courses and improvement courses, promotion of events and spaces for social interaction. In this way, the activities permeate between the conservative and transformative aspects of Environmental Education. Finally, despite the relevance and the various activities found, it is also concluded that there is little academic production and easy access on the topic, therefore, it is expected that this integrative review can guide and assist in studies, research and practices futures of all interested groups.